2019
DOI: 10.1248/bpb.b19-00535
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pathology of Neuropathic Pain and Fibromyalgia

Abstract: Currently, only a few medicines have been approved for use in the clinical treatment of chronic pain, but they are not fully satisfying due to their side effects. From the view that radical treatment, rather than simply treating symptoms, is more important in addressing lifelong chronic pain, we have been investigating translational research for a mechanism-based medicine to treat pain. Through the characterization of various types of peripheral and central neuropathic pain in mice, we discovered that lysophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
0
14
0
2
Order By: Relevance
“…Interestingly, Uchida et al found that LPA production significantly increased within 24 h after the first paclitaxel treatment [ 14 ]. The paclitaxel-induced mechanical allodynia disappeared in LPAR1- and LPAR3- knockout mice [ 14 ], as well as mice pretreated with LPAR1/3 antagonist Ki16425 [ 110 ]. Moreover, significant attenuation of nerve demyelination was also observed in LPAR1-/LPAR3- knockout mice [ 110 ].…”
Section: Lpa and Chemotherapy-induced Neuropathic Pain (Np)mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Uchida et al found that LPA production significantly increased within 24 h after the first paclitaxel treatment [ 14 ]. The paclitaxel-induced mechanical allodynia disappeared in LPAR1- and LPAR3- knockout mice [ 14 ], as well as mice pretreated with LPAR1/3 antagonist Ki16425 [ 110 ]. Moreover, significant attenuation of nerve demyelination was also observed in LPAR1-/LPAR3- knockout mice [ 110 ].…”
Section: Lpa and Chemotherapy-induced Neuropathic Pain (Np)mentioning
confidence: 99%
“…The paclitaxel-induced mechanical allodynia disappeared in LPAR1- and LPAR3- knockout mice [ 14 ], as well as mice pretreated with LPAR1/3 antagonist Ki16425 [ 110 ]. Moreover, significant attenuation of nerve demyelination was also observed in LPAR1-/LPAR3- knockout mice [ 110 ]. In addition, the LPAR5 signaling was shown to enhance microglial migration/cytotoxicity and induced a distinct pro-inflammatory signature via the protein kinase D (PKD) pathway [ 111 ].…”
Section: Lpa and Chemotherapy-induced Neuropathic Pain (Np)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that LPA 1 receptor-and LPA 3 receptormediated amplification of LPA production could be a key mechanism underlying the initiation and maintenance of this pain. Throughout these studies, we found that LPA plays a key role in pain memory, and that LPA 1 receptor-and LPA 3 receptor-antagonists could reverse the established pain, and thereby cure the disease source of pain [28]. Chronicity of neuropathic pain is attributed to increased abundance of inflammatory mediators and ion channel dysfunction leading to afferent nerve sensitization; nerve damage and nerve-glia cross talk have also been implicated [29].…”
Section: Pathophysiology Of Neuropathic Painmentioning
confidence: 97%
“…Peripheral Fibers Increase of peripheral sensitivity Expression of endogenous ligands and receptors on injured nerve target Increase of NF-kB pathway activity Promote the production of leukotriene ▶fig. 1 Pathophysiology of neuropathic pain [21][22][23][24][25][26][27][28][29]. lysophosphatidic acid (LPA), gamma-aminobutyric acid (GABAergic) interneurons, nuclear factor 'kappa-light-chain-enhancer' (NF-κB).…”
Section: Dorsal Root Ganglia Increase Of Calcium Concentration and Nementioning
confidence: 99%